Gendered Neologisms Beyond Social Media: the Current Use of "Mansplaining" - Szymańska, Maria (Research in Language, 2023)
The word mansplaining, which is a linguistic blend of man and explaining, is one of the examples of a trend in the English language of creating gendered neologisms – blends and compounds that add an aspect of gender to the meaning of already existing words that originally are gender-neutral (or appear to be). So far, the linguistic research on this phenomenon has focused on analysing them in informal context of social media (see Bridges 2017, Lutzky and Lawson 2019) or crowd-sourced dictionaries (see Foubert and Lemmens 2018). Nonetheless, with the growing popularity, some gendered neologisms, including mansplaining, start being used in outside social media, in more formal contexts. This study presents the place of mansplaining in the current linguistic landscape through looking at its definitions presented in traditional dictionaries and how it is used outside of social media – in what grammatical forms and in what contexts.